Beneficial Roles of Microglia and Growth Factors in MS, a Brief Review - Pons, Vincent; Rivest, Serge (Frontiers in Cellular Neuroscience, 2020)
Microglia are the brain resident immune cells; they can produce a large variety of growth factors (GFs) to prevent neuronal damages and promote recovery. In neurodegenerative diseases, microglia can play both benefic and deleterious roles, depending on different factors and disease context. In multiple sclerosis, microglia are involved in both demyelination (DM) and remyelination (RM) processes. Recent studies suggest a beneficial role of microglia in regenerative processes. These include the regenerative development of myelin after DM. This review gives an overlook of how microglia and GFs can influence the RM properties.